Detection of Development and Density Urban Build-Up Area with Satellite Image Overlay - Abidin, Muhammad Rais; Arfan, Amal (International Journal of Environment, Engineering and Education, 2019)
The growth dynamics of urban areas and the increase in land requirements are a series of each other influence each other The method used in this study is a quantitative method through spatial analysis using Geographic Information Systems. The purpose of this study was to see the extent to which the development of urban areas using the Urban Index (UI) method. Data analysis carried out by overlapping techniques using a map of the built area of Land Use in 2013 and the results of image interpretation for the built area in 2017. The results of the study showed that there was a percentage increase in the built area from 2013 to 2017 of 12.67%. Then from the total area of Makassar City, around 60.72% of the area built in 2013, and there was a significant increase in 2017 to 76.30%. The process of expansion of built-up land without control often impacts on the loss of land that has ecological functions and then impacts on the emergence of environmental problems. One of the things that can be done to prevent the adverse effects of the development of built land is to monitor and predict its development so that solutions can found before the adverse effects occur.